CHILD PARTICIPATION IN THE PERUVIAN SCHOOL: POSSIBILITIES FOR A CITIZEN CONSTRUCTION OF CHILDREN IN THE DEPARTMENTS OF SAN MARTÍN, CAJAMARCA AND ICA - Javier, Jerjes Loayza (2020)
It is proposed to explore the participatory nature of the school population of the 5th and 6th grade of elementary school in the process of serving rations and products of the National School Food Program of Peru of the level of primary education in the departments of San Martín, Cajamarca and Ica. Through the application of discussion groups and semi-structured interviews, propositive attitudes eager for recognition are noticed, as well as generating solidarity bonds with teachers and student peers. The search for a continuous physical exercise, coupled with the generation of social roles that integrate members into the school, demonstrates the enormous opportunity to envision important quotas for citizen exercise in said participatory process. However, the schools studied do not realize this by inhibiting participation as soon as possibleto exchange children for adults.